The eagle returns : the legal history of the Grand Traverse Band of Ottawa and Chippewa Indians - Fletcher, Matthew L. M. (Michigan State University Press, 2012)
An absorbing and comprehensive survey, The Eagle Returns: The Legal History of the Grand Traverse Band of Ottawa and Chippewa Indians shows a group bound by kinship, geography, and language, struggling to reestablish their right to self-governance. Hailing from northwest Lower Michigan, the Grand Traverse Band has become a well-known national leader in advancing Indian treaty rights, gaming, and land rights, while simultaneously creating and developing a nationally honored Indigenous tribal justice system. This book will serve as a valuable reference for policymakers, lawyers, and Indian people who want to explore how federal Indian law and policy drove an Anishinaabe community to the brink of legal extinction, how non-Indian economic and political interests conspired to eradicate the community's self-sufficiency, and how Indian people fought to preserve their culture, laws, traditions, governance, and language.